Challenges and experience in training intellectually disabled students in the national floristry competition: toward the worldskills competitions - Nadzimah Idris,; Abdul Rahim Razalli,; Mohd Ridhuan Mohd Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysia is one of the 85 member nations competing in the WorldSkills Competition, which unites two-thirds of the world’s population. The WorldSkills mission is to encourage and assist 100 million young people in advancing their skills by 2030. This study investigated how teacher (special education teacher), the community (instructor), and expert, train an intellectually disabled student for the National Floristry Competition. As a precursor for the WorldSkills Competition, this study examined their experiences and difficulties in training intellectually disabled student for this competition. This study uses a purposive sampling method with three participants rather than a random one. Based on a case study research design, it employs ethnographic participant observation and in-depth interviews, among other techniques. The study determined that student with special needs should participate in international skill competitions as early as possible. The Malaysian floristry industry has significant untapped potential, and students with intellectual disabilities can access it if they receive ongoing guidance and training. To be successful in the WorldSkills Competition, Malaysia must overcome financial, time, and knowledge limitations. This study illustrates the difficulties and lessons learned in preparing an intellectually disabled student for the national floristry competition. These empirical investigations result in a deeper understanding and are crucial to academicians as the path for future planning and generating future young talents for the WorldSkills Competition.